The Role of Protein Kinase C During the Differentiation of Stem and Precursor Cells into Tissue Cells - Oliver Pieles; Christian Morsczeck (Biomedicines)
Protein kinase C (PKC) plays an essential role during many biological processes including development from early embryonic stages until the terminal differentiation of specialized cells. This review summarizes the current knowledge about the involvement of PKC in molecular processes during the differentiation of stem/precursor cells into tissue cells with a particular focus on osteogenic, adipogenic, chondrogenic and neuronal differentiation by using a comprehensive approach. Interestingly, studies examining the overall role of PKC, or one of its three isoform groups (classical, novel and atypical PKCs), often showed controversial results. A discrete observation of distinct isoforms demonstrated that the impact on differentiation differs highly between the isoforms, and that during a certain process, the influence of only some isoforms is crucial, while others are less important. In particular, PKCβ inhibits, and PKCδ strongly supports osteogenesis, whereas it is the other way around for adipogenesis. PKCε is another isoform that overwhelmingly supports adipogenic differentiation. In addition, PKCα plays an important role in chondrogenesis, while neuronal differentiation has been positively associated with numerous isoforms including classical, novel and atypical PKCs. In a cellular context, various upstream mediators, like the canonical and non-canonical Wnt pathways, endogenously control PKC activity and thus, their activity interferes with the influence of PKC on differentiation. Downstream of PKC, several proteins and pathways build the molecular bridge between the enzyme and the control of differentiation, of which only a few have been well characterized so far. In this context, PKC also cooperates with other kinases like Akt or protein kinase A (PKA). Furthermore, PKC is capable of directly phosphorylating transcription factors with pivotal function for a certain developmental process. Ultimately, profound knowledge about the role of distinct PKC isoforms and the involved signaling pathways during differentiation constitutes a promising tool to improve the use of stem cells in regenerative therapies by precisely manipulating the activity of PKC or downstream effectors.